Fabrication of mesoporous H3PW12O40/TiO2 composite nanofibers via self-assembly of PS-b-PEO and photocatalytic performance of the resultant fabrics. (June 2019) - Yang, Xuxin; Chen, Zhouli; Zhao, Jingxin; Yu, Ling; Li, Haolong; Chai, Wenqiang; You, Jichun
Abstract: The mesoporous H3 PW12 O40 /TiO2 (nano-HPA/TiO2 ) composite nanofibers were successfully synthesized by electrospinning blend solution of titanium-tetraisopropoxide (TTIP), polystyrene modified HPA (mHPA), polystyrene-block-poly (ethylene oxide) (PS-b-PEO). During electrospinning, the selective distribution of TTIP and mHPA has been induced by self-assembly of block copolymer based on the complexation interaction in PEO/TTIP and the physical entanglement of PS chains in copolymer and mHPA. Calcination of the mHPA/PS-b-PEO/TTIP nanofibers produces mesoporous nano-HPA/TiO2 composite fabrics. Its photocatalytic activity was enhanced remarkably relative to TiO2, which can be attributed to the significant improvement in surface area and separation of the photo-induced electron–hole pairs. Both of them result from the existence of HPA nanoparticles on TiO2 frames in the porous composite nanofibers. Highlights: The selective distribution of mHPA and TTIP was induced by self-assembly of PS-b-PEO. In nano-HPA/TiO2, TiO2 acts as frame while HPA locates at the interface of TiO2 /air. The photocatalytic performance of nano-HPA/TiO2 has been enhanced remarkably.